Alternatif Perbaikan Simpang Tak Bersinyal Berdasarkan Sistem manajemen Lalulintas - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Unsignalized intersection as a part of road system is a node which potentially created traffic problem that cause declining of intersection performance. Intersection between Banda â Belitung streets in Bandung city will perform decrease performance in the year 2003 so that it requires improvement. The improvement will be designed by proposing four alternatives, such as : I) improve geometry and reduce side friction, 2) give additional lane as a tunnel, 3) develop one way system and reduce side friction and 4) change public transport 'oplet/angkoe to mini bus and improve intersection geometry. The selection of intersection improvement is carried out by scoring and ranking some criteria used as selection considerations, i.e.: intersection performance, impact to the road network, environmental impact and accident risk From those alternatives, alternative 2 'give additional lane/tunnel' own highest score, so this is considered as the best alternative for this intersection.